Monetasi Youtube Perspektif Fikih Muamalah - Muhamad Takhim; Ahmad Ifan Fadila; Maskudi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the systematic cooperation agreement between YouTube and YouTuber, fiqh Muamalah's view of the problems arising from the status of the cooperation, the status of the video showing is a clickbait element, as well as the systematic payment of the ad. This study uses qualitative methods with data sources originating from interviews directly to YouTuber and from books, the fatwa of the National Islamic Council of the Indonesian Ulema Council (DSN MUI), records originating from the official YouTube web and journal. The results of this study indicate that the first, the status of the cooperation was indirectly included in the category of Syirkah Abdan because it has fulfilled the pillars, terms, and the provisions found in the Fatwa DSN-MUI No.114 of 2017 concerning Syirkah. Second, the advertising payment system cannot be said to violate Youtuber's justice and violate the sharing of syirkah profits because youtuber is considered aware of Rida for all the provisions when joining the YouTube Partner Program, there is no coercion from YouTube and these provisions are the extra provisions made for all good conditions party.